Economic Impacts of Disasters and Economic Events on Commercial Fishery—The Case of Mississippi Blue Crabs - Benedict C. Posadas (Oceans)
Impact assessments are necessary for supporting fisheries’ disaster applications and management options for states affected by disasters. This paper measures the joint and individual impacts of man-made and natural disasters, global pandemics and recessions, the U.S.-China trade war, and recent increases in fuel prices on commercial dockside values of the Mississippi blue crab fishery. The mean-difference model estimates the direct impacts when the current dockside values fall below the benchmark values. The marine economic recovery model identifies the significant determinants of the variations in the dockside values. Mean-difference model results indicate that the Mississippi blue crab fishery sustained direct losses due to Hurricane Katrina in 2005, the Deepwater Horizon oil spill in 2010, and the opening of the Bonnet Carre Spillway in 2011. The estimated marine economic recovery model explained 93 percent of the variations in real dockside values. Two independent variables are statistically significant, including blue crab landings and time. The disaster variables have the expected signs but are not statistically significant. These methodologies’ usefulness is applicable in assessing the direct impacts on fisheries and other economic sectors affected by disasters such as major hurricanes, oil spills, massive freshwater intrusion, and harmful algal blooms.